Association of Cost and Medical Service Satisfaction with Korean and Conventional Medicine Use before and after Surgery in Postsurgical Patients: A Questionnaire Survey of Korean Patients with Postsurgical Pain Visiting Korean Medicine Hospitals. (19th March 2020) - Lee, Ki-Beom; Lee, Yoon Jae; Kim, Me-riong; Shin, Kyung-Min; Ha, In-Hyuk
Abstract : This study aimed to assess the costs, health status, and medical service satisfaction with Korean and conventional medicine use before and after surgery of patients visiting Korean medicine hospitals for postsurgical musculoskeletal pain. The study population comprised patients who visited KM hospitals for the first time between June and November 2017 for persistent or recurrent pain and discomfort after low back, neck, shoulder, or knee surgery. Various validated questionnaires were used to collect data. A total of 100 participants were enrolled, and the majority had undergone low back surgery ( n = 82). The participants had received 1.3 ± 0.7 magnetic resonance imaging (MRI) examinations and 2.4 ± 2.8 X-rays before surgery. Conventional interventions used before surgery were physical therapy (43%), medications (34%), and injections (28%), in descending order, while 48% of patients reported having received acupuncture 51.3 ± 81.1 times. The mean satisfaction score for surgery was 5.5 ± 2.8 points based on a 9-point Likert scale, while that for KM-based interventions was 6.3 ± 1.7 points. With respect to health-related information, the mean scores were 6.0 ± 2.2 points on the Numeric Rating Scale (NRS), 0.6 ± 0.2 points on the 5-Level EuroQol-5 Dimension (EQ-5D-5L), and 15.3 ± 10.2 on Beck's Depression Index II (BDI-II). The mean score on the Oswestry Disability Index (ODI) in patients with low back pain was 40.1 ± 19.2 points. Work impairment, as measured using the Work Productivity and Activity Impairment Questionnaire: General Health (WPAI-GH), was 62.5 ± 47.8%, while activity impairment was 5.9 ± 2.6%. Participants tended to show low satisfaction regarding surgery and high preference for KM-based interventions. In particular, low back surgery patients reported high ODI scores, indicating high dysfunctional levels and poor prognosis after surgery. It can be inferred that it is therefore important to provide appropriate presurgical and postsurgical care for patients with musculoskeletal pain to improve pain, function, and quality of life.